2021
DOI: 10.1021/acs.jctc.1c00114
|View full text |Cite
|
Sign up to set email alerts
|

Metadynamics-Based Approaches for Modeling the Hypoxia-Inducible Factor 2α Ligand Binding Process

Abstract: Several methods based on enhanced-sampling molecular dynamics have been proposed for studying ligand binding processes. Here, we developed a protocol that combines the advantages of steered molecular dynamics (SMD) and metadynamics. While SMD is proposed for investigating possible unbinding pathways of the ligand and identifying the preferred one, metadynamics, with the path collective variable (PCV) formalism, is suggested to explore the binding processes along the pathway defined on the basis of SMD, by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…59−62 In a recent work, we investigated the unbinding of the THS-020 ligand from the HIF-2α PAS-B domain through SMD simulations. 63 50 constant velocity SMD replicas of 25 ns each were used to pull the ligand along the selected CV, namely, the distance between the center of mass of the amino acid atoms lining the cavity and the center of mass of the ligand. The simulations analyzed in this work are those along the preferred entrance to the cavity identified in the previous work (reported as "path 1").…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…59−62 In a recent work, we investigated the unbinding of the THS-020 ligand from the HIF-2α PAS-B domain through SMD simulations. 63 50 constant velocity SMD replicas of 25 ns each were used to pull the ligand along the selected CV, namely, the distance between the center of mass of the amino acid atoms lining the cavity and the center of mass of the ligand. The simulations analyzed in this work are those along the preferred entrance to the cavity identified in the previous work (reported as "path 1").…”
Section: ■ Resultsmentioning
confidence: 99%
“…For the sake of comparison with the free-energy landscape previously identified by the MetaD calculation, 63 we mapped the frames belonging to each free-energy basin on the SOM (Figure S10). We found that conformations belonging to each of these basins generally map in few close neurons, belonging to the same cluster on the map.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Metadynamics with Path Collective Variables. The PCV metadynamics simulation 48,49 is performed to provide a more accurate estimation of the free energy change with respect to the DFG flipping process along the two discovered translation paths. The parameter settings are the same as described in the Metadynamics Setting subsection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, however, there are no experimental methods that would enable such dynamic process characterisation at a molecular scale. Lately, in-silico techniques have emerged as a viable alternative to experimental methods and are becoming increasingly effective in providing atomic-level description of protein-ligand interactions [38][39][40][41][42][43][44][45][46][47] . Dynamic processes like these are typically studied using molecular dynamics (MD) simulations, however, ligand binding/unbinding is a rare event that can be hard to sample within a reasonable time [48,49] .…”
Section: Introductionmentioning
confidence: 99%
“…This approach leads to a significantly improved exploration of the simulation space, and, once the exploration is complete, an efficient reconstruction of the free energy surface (FES) as a function of the CVs used [57,58] . MetaD in its various modifications has been applied in numerous ligand-protein binding studies [38][39][40][41][42][43][44][45][46][47] . One of these MetaD variations is funnel metadynamics (FMetaD), where a funnel shaped restraint potential is applied to the system to reduce the space explored by the ligand once it is unbound, thus reducing computational cost even more [46,[59][60][61][62][63] .…”
Section: Introductionmentioning
confidence: 99%